2013
DOI: 10.1126/science.1238303
|View full text |Cite
|
Sign up to set email alerts
|

Tight Coordination of Protein Translation and HSF1 Activation Supports the Anabolic Malignant State

Abstract: A unifying characteristic of aggressive cancers is a profound anabolic shift in metabolism to enable sustained proliferation and biomass expansion. The ribosome is centrally situated to sense metabolic states but whether it impacts systems that promote cellular survival is unknown. Here, through integrated chemical-genetic analyses, we find that a dominant transcriptional effect of blocking protein translation in cancer cells is complete inactivation of heat shock factor 1 (HSF1), a multifaceted transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
255
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(270 citation statements)
references
References 50 publications
12
255
1
2
Order By: Relevance
“…We cannot discount the possibility of a direct role for HSP70 itself contributing to the regulation observed in the present study, because it has been reported that HSP70 can block HSF1 activation through stabilization of a HSF1-HSP70 complex (28). However, in a recent elegant study, Santagata and colleagues provided compelling evidence that regulation of HSF1 transcriptional activity was intimately linked to translational flux (29). When protein translation was blocked in breast cancer cells, the strongest transcriptome changes included a category of genes with promoters containing consensus HSF1-binding sites.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We cannot discount the possibility of a direct role for HSP70 itself contributing to the regulation observed in the present study, because it has been reported that HSP70 can block HSF1 activation through stabilization of a HSF1-HSP70 complex (28). However, in a recent elegant study, Santagata and colleagues provided compelling evidence that regulation of HSF1 transcriptional activity was intimately linked to translational flux (29). When protein translation was blocked in breast cancer cells, the strongest transcriptome changes included a category of genes with promoters containing consensus HSF1-binding sites.…”
Section: Discussionmentioning
confidence: 61%
“…Similar to what was observed following BEZ235 treatment in our study, the inducible HSP70-encoding HSPA1A gene was among the 10 most downregulated transcripts. Furthermore, using a gene signature-based genetic screen, they showed that the perturbations that most positively correlated with the HSF1 inactivation gene signature were highly enriched for translation inhibitors (such as cycloheximide) and compounds targeting signal pathways that regulate protein translation, including PI3K/mTOR (29). mTOR controls protein synthesis through two distinct but interconnected downstream pathways: via activation of the 70 kDa ribosomal protein S6 kinase 1 (p70 S6K1 ) and its substrate ribosomal protein S6, and through phosphorylative inactivation of 4EBP1, a repressor of translation initiation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights general principles for drug targeting and provides foundations for structure-based drug design. These structures will facilitate the development of next-generation antibiotics with reduced adverse effects and new therapeutics against infectious diseases, cancers and genetic disorders caused by premature termination codons [8][9][10][11][12] . High-resolution X-ray crystallography of the 80S ribosome opens a new area of investigation-a large number of ribosome inhibitors certainly remain to be discovered and analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the eukaryotic ribosome is a major target for broad-spectrum and eukaryote-specific small-molecule inhibitors isolated from natural sources. Despite limited understanding of their molecular mechanism, eukaryote-specific ribosomal inhibitors are increasingly used in research and hold potential for new therapeutics against a wide range of infectious diseases, cancers and genetic disorders [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…Consistent with its versatile functions in the regulation of numerous transcriptional programs, HSF1 also has been implicated in certain pathological conditions that include neurodegeneration and cancer (16,17). Although HSF1 may not be strictly required for normal cellular or organismal survival in mammals (18), the role of HSF1 in regulating non-HSR targets, including those related to DNA damage repair and the cell cycle, recently has emerged as critical for cancer cell survival (19)(20)(21). Thus, inhibiting the activity of HSF1 has been suggested as a potential anticancer therapeutic approach (22).…”
mentioning
confidence: 99%